2017
DOI: 10.1364/prj.5.000372
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of ghost imaging of reflective objects with different surface roughness

Abstract: We present an experimental demonstration of ghost imaging of reflective objects with different surface roughness. The influence of the surface roughness, the transverse size of the test detector, and the reflective angle on the signal-to-noise ratio (SNR) is analyzed by measuring the second-order correlation of the light field based on classical statistical optics. It is shown that the SNR decreases with an increment of the surface roughness and the detector's transverse size or a decrease of the reflective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Experiments are designed to verify the above analysis of the performance of binary sampling GI. For the conventional GI setup [27,28], as shown in Fig. 3.…”
Section: Performance Analysismentioning
confidence: 99%
“…Experiments are designed to verify the above analysis of the performance of binary sampling GI. For the conventional GI setup [27,28], as shown in Fig. 3.…”
Section: Performance Analysismentioning
confidence: 99%
“…Cheng and Han studied a particular aspect of coincidence imaging with incoherent source by using classical statistical optics [7]. After that, theoretical and experimental CI schemes exploiting the correlation of two classical beams obtained by splitting incoherent thermal source were proposed [9][10][11][12][13][14][15][16][17]. Furthermore, many relevant results including high-order [18,19], computational [20,21], differential [22], and compressive sensing [23,24] were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have explored the effects of the roughness on the GI, and experimental results demonstrated that the signal-to-noise ratio (SNR) of GI decreases along with the increase of surface roughness. 17,18 As everyone knows, when the difference of the reflectivity or transmittance between objects and background is not apparent, it is difficult for conventional imaging to distinguish them, especially underwater. When the light transferring in the water, the energy will be attenuated or absorbed due to underwater dissolved organic matter and suspended particles, but some proposed method can produce reliable and promising results.…”
Section: Introductionmentioning
confidence: 99%